Financial Literacy and Digital Finance: Determinants of MSMEs Sustainability in Ternate City - Adam, Mukhtar A.; Fala, Dwi Yana Amalia Sari; Nurdin, Nurdin; Zainuddin, Zainuddin (Cita konsultindo, 2025)
This study aims to analyze the effect of financial literacy and digital finance on the sustainability of MSMEs in Ternate City. Data in this study are the owners/managers of SMEs in Ternate City. Collecting data using a questionnaire to 115 respondents. Data analysis using multiple regression analysis. The Financial literacy variable was measured using education (a combination of formal and non-formal education levels). This study shows that financial literacy has no significant effect on the sustainability of MSMEs, while digital finance offers substantial results. In addition, this study also finds that variations in training have an impact on increasing financial literacy on the sustainability of MSMEs. Theoretically, this research contributes to the latest view on the measurement of financial literacy. In addition, these findings support research related to financial literacy, digital finance, and the sustainability of MSMEs. Finally, from a practical point of view, this study provides a policy direction for the government in policymaking, especially in improving human resources with technical support to ensure the quality and sustainability of MSMEs.